CODE COMPRESSION FOR THE EMBEDDED ARM/THUMB PROCESSOR - Xu, Xianhong; Jones, Simon (International Journal of Computing, 2014)
Previous code compression research on embedded systems was based on typical RISC instruction code. THUMB from ARM Ltd is a compacted 16-bits instruction set showing a great code density than its original 32-bits ARM instruction. Our research shows that THUMB code is compressible and a further 10-15% code size reduction on THUMB code can be expected using our proposed new architecture – Code Compressed THUMB Processor. In our proposal, Level 2 cache or additional RAM space is introduced to serve as the temporary storage for decompressed program blocks. A software implementation of the architecture is proposed and we have implemented a software prototype based on ARM922T processor, which runs on the ARMulator.